Fostering creative problem solving skills through integrated learning of volcanic eruption disasters - Fanny Rahmatina Rahim; Ahmad Fauzi; Syafriani (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This article aimed to describe how an integrated learning approach can enhance creative problem-solving abilities within the context of studying volcanic eruption disasters. Volcanic eruptions are complex natural phenomena that require deep understanding and creative thinking skills to address. In this study, a descriptive literature review was conducted to gain a comprehensive understanding of the key findings and insights related to integrated learning and creative problem-solving in the context of volcanic eruption disasters. The review focused on articles published between 2013 and 2023 that specifically addressed creative thinking abilities and integrated learning approaches for volcanic eruption disasters. To gather relevant articles, databases such as Google Scholar, Emerald, ScienceDirect, IEEE, and Springer were utilized. The literature review reveals that integrated learning approach can serve as an effective means to develop students' creative problem-solving abilities within the context of studying volcanic eruption disasters. By utilizing strategies such as inquiry-based learning, technology integration, and interactions with stakeholders, students can enhance their creative thinking skills, improve their holistic understanding, and be prepared to tackle the complexities of challenges related to volcanic eruptions. The implication of this research highlights the importance of implementing an integrated learning approach in the curriculum to enhance students' creative problem-solving skills in addressing complex natural disasters such as volcanic eruptions.